Association between children's home-schooling and parental psychological distress during the COVID-19 pandemic in Taiwan: Risk and protective factors in a multilevel approach - Chin-Wan Wang; Hsin-Hui Lu; Jao-Shwann Liang; Duan-Rung Chen; Chia-Chun Chen (Elsevier, 2023)
Background: The role home-schooling of children in parental mental health during the COVID-19 pandemic in Taiwan remains unknown. This study aimed to assess the association between parental psychological distress and home-schooling in a socio-ecological context during the peak of the first wave of the COVID-19 pandemic in Taiwan. Methods: This was a prospective cohort study. In total, 902 parents (father: n = 206, mother: n = 696) who home-schooled children under 18 years of age were recruited by purposive sampling from 17 cities in Taiwan. Data were collected between 19 July and 30 September 2021 through a survey. Multilevel regression models were used to examine the association between parents' psychological distress and home-schooling considering the characteristics at the person and city levels. Results: Parental psychological distress was positively associated with difficulty in setting up electronic devices and increased disputes between parents and children, and it was negatively associated with time management and increased time spent bonding with their children during home-schooling (Ps < 0.05). Parents who had a child with health conditions, lived in an extended family, worked from home, lived during the Level 3 alert level, and lived with a median/sporadic level of the COVID-19 community spread by city also reported greater psychological distress (Ps < 0.05). However, parents who had greater household family support reported less psychological distress (P < .05). Conclusions: Clinicians and policy makers must carefully consider parental mental health while home-schooling during the COVID-19 pandemic in a broader socio-ecological context. A focus is advised on the home-schooling experiences of parents and other risk and protective factors for parental psychological distress at the person and city levels, especially for those with children who require medical interventions and have a medical condition.